Cambridge English IELTS 12 academic with answers : (Cambridge University press, 2017)
The Student’s Book with answers allows students to familiarise themselves with IELTS and to practise examination techniques using authentic tests. It contains four complete tests for Academic candidates. An introduction to these modules is included in the book, together with an explanation of the scoring system used by Cambridge English Language Assessment. There is a comprehensive section of answers and tapescripts at the back of the book. Audio CDs containing the material for the Listening Tests, and a Student’s Book with answers with downloadable Audio are sold separately.